Pengaturan dan Penerapan Prinsip Teritorial dalam Perlindungan Indikasi Geografis Indonesia (Dalam Perspektif Hukum Internasional dan Nasional) - Dayu Medina; Dewi Enggriyeni (UNES Law Review, 2023)
The principle of territoriality is one of the fundamental principles in Intellectual Property Rights (IPR) which is regulated in Trade Related Aspects of Intellectual Property Rights (TRIPS). This principle gives authority to the state to regulate IPR according to the circumstances and needs of the state. This territorial principle allows a country to design intellectual property laws in a way that is consistent with its goals. This study uses a normative juridical method with a statutory and comparative law approach. Regulations regarding territorial principles in the regulation of Geographical Indications (GI) are contained in Article 22 (1) TRIPs, where TRIPs are the basis for the rules (minimum standards) for regulating GI protection. In addition, GI protection is contained in the Lisbon Agreement for the Protection of Appeals of Origin and their International Registration 1958 and in the Madrid Protocol. Indonesia regulates GI protection in Law Number 20 of 2016 concerning Trademarks and Geographical Indications and in Government Regulation Number 12 of 2019 concerning Geographical Indications. Indonesia must regulate GI well because it has great potential to increase people's income. Apart from that, Indonesia must also register Indonesian GIs in the international registration room, so that there is no misuse in their use.